PENGUATAN EKONOMI LOKAL MELALUI DIGITALISASI UMKM PEREMPUAN: STUDI KASUS KELOMPOK TANI WANITA DESA SIDODADI - Farida Rahmawati; Etty Soesilowati; Magistyo Purboyo Priambodo; Lustina Fajar Prastiwi (Jurnal AbdiMas Nusa Mandiri, 2025)
Strengthening the local economy through the active role of the Women Farmers Group (KTW) by improving digital marketing technology skills is an effective strategy for developing rural MSMEs. Sidodadi Village in Malang Regency has several key agricultural commodities such as bananas, cassava, and corn, which are mostly processed and marketed by women’s MSME groups. However, several challenges remain, including limited institutional management capacity, lack of knowledge about digital marketing technology, and restricted market access, making it difficult for MSMEs to compete. This community service aims to assist the Women Farmers Group in improving institutional management capacity and digital marketing skills through training and mentoring activities. The program was conducted in Sidodadi Village using survey, socialization, and training methods, followed by evaluation. The evaluation results show that participants were enthusiastic, actively involved, and demonstrated improved understanding and skills in using digital marketing tools. The activity successfully encouraged the group to optimize digital marketing for the sustainable growth of rural MSMEs. Therefore, this service is expected to increase the efficiency of agricultural product marketing and positively impact community welfare and income.